Implications of the SNHG10/miR-665/RASSF5/NF-κB pathway in dihydromyricetin-mediated ischemic stroke protection - Zeng,Qi; Xiao,Yan; Zeng,Xueliang; Xiao,Hai (PeerJ, 2024)
Ischemic stroke (IS) remains a leading cause of disability and mortality worldwide, and inflammation and oxidative stress play significant roles in its pathogenesis. This study investigates the effects of dihydromyricetin (DHM) on IS using RT-qPCR and western blot with SH-SY5Y cells, focusing on its effects on the small nucleolar RNA host gene 10 (SNHG10)/microRNA (miR)-665/Ras association domain family member 5 (RASSF5) axis and nuclear factor-kappa B (NF-κB) signaling. In addition, the effects of the SNHG10/miR-665/RASSF5 axis on SH-SY5Y cell activity, apoptosis, oxidative stress, and inflammatory markers were analyzed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, flow cytometry, and enzyme-linked immunosorbent assays. Our results showed that, in response to oxygen-glucose deprivation/reperfusion (OGD/R), DHM treatment improved cell viability, reduced apoptosis, and attenuated neuroinflammation and oxidative stress in a dose-dependent manner (p < 0.05). Interestingly, lncRNA SNHG10 was overexpressed during OGD/R and suppressed by DHM. Through bioinformatics analysis and experimental validation, we identified miR-665 as a direct target of SNHG10 and RASSF5 as a direct target of miR-665. The protective effect of DHM against OGD/R injury was partially reversed by SNHG10 overexpression and further enhanced by co-transfection with the miR-665 mimic and si-RASSF5 (p < 0.05). This study identifies a novel mechanism of DHM against IS, which may act via modulation of the SNHG10/miR-665/RASSF5 axis and inactivation of NF-κB signaling, and offers a promising therapeutic target for IS.
Keywords: Ischemic stroke; Dihydromyricetin; SNHG10; RASSF5; miR-665